Pengalaman Pemenuhan Zat Gizi pada Ibu dengan Riwayat Anemia Kehamilan: Studi Kualitatif: The Experiences of Nutrition Fulfillment in Mothers with a History of Anemia During Pregnancy: A Qualitative Study - Syoifa Rahmawati; Restuning Widiasih; Ida Maryati; Yanti Hermayanti; Ermiati Ermiati; Windy Natasya (Universitas Airlangga, 2023)
Background: Anemia during pregnancy is one of the most common disorders, especially in middle and poor economic countries, including Indonesia. Anemia is closely related to nutrition consumed during pregnancy. Objectives: This research aimed to explore the experience of nutritional fulfillment in pregnant women with a history of anemia during pregnancy. Methods: The research used a qualitative design with a phenomenological approach. The sampling technique used was purposive sampling with inclusion criteria, so a sample of 20 pregnant women with a history of anemia was obtained. Data collection was carried out through semi-structured in-depth interviews. Data analysis used the Colaizzi method. Results: The results showed five themes: lack of intake and diversification of food types during pregnancy; food processing with hot temperatures and dry intensity reduces the nutritional value of food; choosing the type of food without knowing its benefits can affect health; several types of vegetables, fruit, and protein are dietary restrictions during pregnancy; and non-compliance in consuming Fe tablets regularly. Fulfillment of nutritional status is essential for pregnant women and must be fulfilled thoroughly so that anemia does not occur during pregnancy. Conclusions: Mothers' lack of knowledge and inability to care for themselves during pregnancy. Lack of information, starting from the selection, processing, and consumption of food during pregnancy, can increase the mother's health risks, including anemia. Pregnant women must improve prenatal care to get education about fulfilling nutrition during pregnancy.